Teachers’ and Students’ Perceptions on the Acquisition of Competences Through Project-Based Learning (Pbl) in Bilingual Education - Sánchez García, Rosa (Journal of English Studies, 2023)
Project Based Learning (PBL) has recently acquired a paramount role in education with a new respectability and a burgeoning number of proponents. Its envisaging as an instructional approach that embraces the basic concepts of research, reflection, production, complexity and rigor when dealing with relevant issues for students and society has led to PBL being heralded as a transformational educative strategy and a catalyst of competences. However, there is scanty research on students and teachers’ perceptions of Project-Based instruction and Content and Language Integrated Learning (CLIL) run in parallel. This article aims to report the findings of a research study conducted in three primary and secondary schools in Seville (Spain) to investigate the level of competence development achieved by students when working through a project in a bilingual learning context. The study has been conducted in a hybrid way with quantitative and qualitative method following an exploratory survey-type methodology for which two ad hoc questionnaires have been designed, addressed and adapted to the two sample units selected for our study: teachers and students. The results of this study suggest that project work activates a range of skills that can be transferred to real-life situations, enabling students to become socially and academically competent, being likewise a promising activity to socialize and promote language learning.